Teachers’ Personal Competence and Students’ Learning Motivation in Study English on Luring Learning Model During Pandemic Covid-19: A Correlational Study - Hakim, M. Arif Rahman; Sulastri, Vira; Andriadi; Astari, Ade Riska Nur; Rahimi, Mahmood (Proceeding International Conference on Education, 2024)
This study aims to determine the correlation between the teachers’ personal competence and students’ learning motivation. This research employs a quantitative, correlational method. The study's population comprised all students from Madrasah Aliyah Pancasila Bengkulu, with a total sample size of 66 students from 3 classes. The research and calculation results indicate that the personal competence of the teachers at MA Pancasila Bengkulu meets the "good" criteria, with a frequency of 57 and a percentage of 86.36%. At MA Pancasila Bengkulu, students' learning motivation falls into the "medium" category, with a frequency of 36 and a percentage of 54.55%. Researchers used a two-variable correlation test to find a link between teachers' personal competence and students' motivation to learn. The Pearson Correlation coefficient was (+) 0.354, which is 35.4%, and the coefficient of determination (r²) was (0.354) ²=0.125, which is 12.5%. This means that the teachers’ personal competence variable has an effect of 12.5% on students' learning motivation.